2002
DOI: 10.1042/bj20020254
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in germ cell apoptosis induced by di(2-ethylhexyl)phthalate

Abstract: Phthalate esters have been used extensively as plasticizers of synthetic polymers. Recent studies have revealed that these esters induce atrophy of the testis, although its pathogenesis remains unknown. The present study describes the possible involvement of oxidative stress in the pathogenesis of atrophy of the rat testis induced by di(2-ethylhexyl)phthalate (DEHP). Biochemical and immunohistochemical analysis revealed that oral administration of DEHP increased the generation of reactive oxygen species, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(159 citation statements)
references
References 47 publications
5
154
0
Order By: Relevance
“…Sperm counts in healthy men around the world have fallen by about 50 per cent in the last 50 years in the Western world (Auger et al, 1995;Kasahara et al, 2002). This may be attributed to the insufficient spermatozoa (oligozoospermia) or the lack of spermatozoa (azoospermia) (Yazama et al, 2006).…”
Section: Infertility Oxidative Stress and Vitamin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm counts in healthy men around the world have fallen by about 50 per cent in the last 50 years in the Western world (Auger et al, 1995;Kasahara et al, 2002). This may be attributed to the insufficient spermatozoa (oligozoospermia) or the lack of spermatozoa (azoospermia) (Yazama et al, 2006).…”
Section: Infertility Oxidative Stress and Vitamin Cmentioning
confidence: 99%
“…The male factor is responsible for 25 % of these cases (Sharlip et al, 2002;Liu et al, 2006;Agarwal et al, 2008). One male infertility mechanism is the excess production of reactive oxygen species (ROS) in sperm (Sharma & Agarwal, 1996;Chen et al, 2001;Kasahara et al, 2002;Agarwal et al, 2008). This induces nuclear DNA fragmentation, lipid peroxidation and protein cross links and results in cell death (Alvarez et al, 1987;Steenken, 1989;Tramer et al, 1998;Liu et al, 2006).…”
Section: Infertility Oxidative Stress and Vitamin Cmentioning
confidence: 99%
“…Because some studies have suggested that DEHP-induced elevation of oxidative stress contributes to hepatotoxicity and testicular toxicity (23)(24)(25), the influence of oxidative stress in DEHP-induced glomerulonephritis was examined. Immunoblot analysis showed that total amounts of 4-HNE-modified proteins, a lipid peroxidation marker, were increased markedly and dosage dependently in glomeruli of DEHP-exposed PPAR␣-null mice at 22 mo but increased only mildly in exposed wild-type mice ( Figure 5A).…”
Section: Dehp Elevates Oxidative Stress In Glomerulimentioning
confidence: 99%
“…The increased generation of ROS often observed in older men [37][38][39], may be due to several factors and include routine medical prescription and environmental pollutants [58]. The generation of ROS could be made worse by infection, prolonged stasis and abnormal spermatozoa, environmental and life style changes [44,45,[59][60][61] .…”
Section: Extrinsic Factorsmentioning
confidence: 99%